Two-year performance of Acacia crassicarpa provenances at Serdang, Malaysia - Awang, Kamis; Ab Shukor, Nor Aini; Senin, Abd Latib (Universiti Putra Malaysia Press, 1995)
A trial of eight provenances of Acacia crassicarpa A. Cunn. ex Benth. was assessed for survival and growth at age two years. Three provenances were from northern Queensland, Australia, four from Papua New Guinea and one from Irian Jaya, Indonesia. All provenances survived well (> 94 %), but they differed significantly (P < 0.01) in their growth performance. All provenances had more than 43% of their trees with single stems. For timber production, the provenance from Irian Jaya (Samlleberr) and two provenances from Queensland.(Olive River and Jardine River-Bamaga) were identified as promising.